GROWTH REVIVAL OF GREY OYSTER (PLEUROTUS PULMONARIUS) POWDER CULTURE MUSHROOM FROM THE EFFECT OF SPRAY DRYING TEMPERATURE - Zarina Zakaria; Fatihah Aziz; Mohd Sharizan Md Sarip; Noor Hasyierah Mohd Salleh (International Islamic University Malaysia Engineering Journal, 2024)
In mushroom cultivation, spawn is among the most important factors that ensure a successful production. Considering several drawbacks from both solid and liquid spawn in shelf life and preservation matters, it is suggested that the dry powder form of spawn is a good potential to explore. A study of powder culture formation using a spray dryer involved various inlet temperatures of 80 oC, 90 oC, 100 oC, 110 oC, 120 oC and 130 oC. The yield % of the dried powder culture was measured and it was found that 130 oC yielded the highest percentage of 50.33%. The lowest temperature yielded the lowest percentage. On the other hand, the lowest temperature of 80 oC revived the highest mycelium dry weight at 1.68 g which was obtained on the 10th day of the incubation periods. The revival ability was decreased with the increase of temperature. The study proved that the powder culture of P. pulmonarius was able to perform and revive whereby it holds a potential to be preserved over a longer period, which is beneficial for the mushroom cultivator.